Globalization and Militarism: Feminists Make the Link (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
Review of Globalization and Militarism: Feminists Make the Link by Cynthia Enloe. 2ed. New York, Rowman & Littlefield Publishers, 2016, ix + 216pp., $99.00 (hardcover), ISBN 978-1-4422-6543-1.